2004
DOI: 10.1210/me.2003-0467
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Interferon-γ and Progesterone Signaling Pathways in Human Endometrium: Role of PIASy (Protein Inhibitor of Activated Signal Transducer and Activator of Transcription-y)

Abstract: All cardinal events during the reproductive cycle, including ovulation, implantation, and menstruation, are characterized by a profound tissue remodeling and an associated local inflammatory response. The ovarian hormone progesterone is a key modulator of inflammatory signals in reproductive tissues, but the underlying mechanisms are not well understood. In this study, we report that differentiating human endometrial stromal cells (ESCs) acquire resistance to interferon-gamma (IFNgamma)-dependent signal transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 53 publications
7
22
0
Order By: Relevance
“…2A), in agreement with previous reports (2). This was in contrast to Piasy, which, in the absence of treatment, presented predominantly nuclear staining, in agreement with previous observations of endogenous Piasy localization (34) and the general description of PIAS family members such as nuclear proteins (35) These colocalization experiments demonstrate that Piasy and Trim32 can interact in mammalian cells, and suggested Pictures of the plates were taken after 5 days of culture at 30°C. B, summary of the interactions between Trim32 and members of the PIAS family as determined in the yeast two-hybrid assay, using the same methods as in A.…”
Section: Trim32supporting
confidence: 92%
See 1 more Smart Citation
“…2A), in agreement with previous reports (2). This was in contrast to Piasy, which, in the absence of treatment, presented predominantly nuclear staining, in agreement with previous observations of endogenous Piasy localization (34) and the general description of PIAS family members such as nuclear proteins (35) These colocalization experiments demonstrate that Piasy and Trim32 can interact in mammalian cells, and suggested Pictures of the plates were taken after 5 days of culture at 30°C. B, summary of the interactions between Trim32 and members of the PIAS family as determined in the yeast two-hybrid assay, using the same methods as in A.…”
Section: Trim32supporting
confidence: 92%
“…Nucleocytoplasmic Redistribution of Piasy and Interaction with Trim32 in the Cytoplasm-We and others have reported that Trim32 is localized in cytoplasmic speckles (2,8), whereas Piasy and PIAS family members in general are considered nuclear proteins (34,35). Thus, it was important to determine the subcellular localization of the interaction of Trim32 and Piasy.…”
Section: Trim32mentioning
confidence: 99%
“…We have recently reported an inverse regulation of the IFN-g-R and its signaling response through STAT-1 in human ESCs during decidualization (12). In line with these observations, another study observed that decidualizing ESCs acquire a reduced responsiveness to IFN-g due to a convergence of IFN-g and P signaling (13).…”
supporting
confidence: 65%
“…A possible dosedependency or the involvement of other signaling pathways might be an explanation for this observation. Nevertheless, the lack of effects of heparin on Nmi probably does not have many functional consequences as Nmi does not enhance IFN-g-dependent transcription in decidualized ESCs (13).…”
Section: Figurementioning
confidence: 99%
“…Furthermore, a recent study observed the convergence of IFN-␥ and P4 signaling pathways in endometrial stromal cells and demonstrated that progesterone was able to antagonize the signaling pathways of IFN-␥ (36).…”
Section: Cd56mentioning
confidence: 98%